A highly focused antigen receptor repertoire characterizes γδ T cells that are poised to make IL-17 rapidly in naive animals - Wei, Yu-Ling; Han, Arnold; Glanville, Jacob; Fang, Fengqin; Zuniga, Luis A.; Lee, Jacob; Cua, Daniel; Chien, Yueh-Hsiu (Frontiers in Immunology, 2015)
Interleukin (IL)-17 plays a key role in immunity. In acute infections, a rapid IL-17 response must be induced without prior antigen exposure, and γδ T cells are the major initial IL-17 producers. In fact, some γδ T cells make IL-17 within hours after an immune challenge. These cells appear to acquire the ability to respond to IL-1 and IL-23 and to make IL-17 naturally in naïve animals. They are known as the natural Tγδ17 (nTγδ17) cells. The rapidity of the nTγδ17 response, and the apparent lack of explicit T cell receptor (TCR) engagement for its induction have led to the view that this is a cytokine (IL-1, IL-23)-mediated response. However, pharmacological inhibition or genetic defects in TCR signaling drastically reduce the nTγδ17 response and/or their presence. To better understand antigen recognition in this rapid IL-17 response, we analyzed the antigen receptor repertoire of IL-1R+/IL-23R+ γδ T cells, a proxy for nTγδ17 cells in naïve animals, using a barcode-enabled high throughput single-cell TCR sequence analysis. We found that regardless of their anatomical origin, these cells have a highly focused TCR repertoire. In particular, the TCR sequences have limited V gene combinations, little or no junctional diversity and much reduced or no N region diversity. In contrast, IL-23R- cells at mucosal sites similar to most of the splenic γδ T cells and small intestine epithelial γδ lymphocytes expressed diverse TCRs. This remarkable commonality and restricted repertoire of IL-1R+/IL-23R+ γδ T cells underscores the importance of antigen recognition in their establishment/function.